SOCIAL REINTEGRATION AND MISSIONARY WORK: A PSYCHOLOGICAL PERSPECTIVE - Jatay Mota Garros, João Guilherme; Xavier Portela, Letícia; Gomes Lopes, Fernanda (Cadernos ESP, 2025)
This experience report, conducted by psychology students in Fortaleza, investigated the impact of religiosity on identity construction and coping with adversity among men in missionary training. Originating from homelessness and with a history of psychoactive substance use, the participants were engaged in a Catholic social reintegration program. Using participant observation and focus groups with the "Wheel of Life" tool, the qualitative research revealed significant improvement in fulfillment, happiness, purpose, and social life following religious engagement. The Christian organization served as a catalyst for transformation, offering support and meaning-making to the assisted individuals. It is concluded that religiosity emerges as an essential resource for alleviating suffering and re-signifying life, grounded in respect and non-stigmatization of vulnerable individuals. The field experience was fundamental for the theoretical and human development of the psychology students.
Keywords: Psychology; Religion; Focus Groups